Students’ Engagement in Video-Recorded Presentation to Enhance Public Speaking Skills during COVID-19 Outbreak - Hardiningsih, Sri; Aswani, Aprilza; Amalo, Elizabeth Anggraeni; Yusuf, Muhammad; Anggraeni, Dewi; Pandiya, Pandiya (UNIB Press, 2025)
This study aimed to explore the synergistic integration of these competencies within the context of Business English education, particularly relevant during the COVID-19 pandemic's shift to online instruction. This study involved 23 vocational students aged 21-23 who were tasked with watching model public speaking videos and subsequently creating and recording their own presentations. Data was collected through questionnaires and in-depth interviews, revealing that this video-recording task significantly benefited students by enabling them to identify their individual misconceptions about public speaking, actively engage in self-directed learning strategies, and demonstrably improve their overall public speaking proficiency. These findings underscore the potential of incorporating such video-based assignments in online language learning environments to foster both independent learning and enhanced communication skills. Furthermore, our research discusses the pedagogical implications of these results for educators and suggests avenues for future research in the fields of language education and online learning, emphasizing the value of combining self-assessment through recording with autonomous learning principles to enhance communicative competence.